Young Immunocompetent Individual Positive for Histoplasma Capsulatum on Bronchoalveolar Lavage Fluid Cytology - Afsar, Nabila; Zareen, Maseera; Afroze, Idrees Akhtar; Begum, Atiya (Annals of Pathology and Laboratory Medicine, 2019)
Primary pulmonary histoplasmosis is a lung disease caused by dimorphic fungus Histoplasma Capsulatum. Bronchoalveolar fluid cytology is routinely performed as an inexpensive test even in under equipped laboratories. A 26 year old female, presented with persistent cough, evening rise of temperature and generalised weakness since 3 months and streaky hemoptysis since 3 weeks. CT showed consolidation in lower lobe of left lung and multiple mediastinal nodes in perivascular (aortic arch ) region and in sub carinal region. Bronchoscopy showed purulent exudates in lower lobe (6th segment of left lung). Bronchoalveolar lavage fluid was obtained and subjected to cytological evaluation and microbiological examination for Acid Fast bacillus. Cytosmears revealed macrophages with engulfed clusters of single walled yeast cells. The suspicion of Histoplasma was raised and the fluid was sent for fungal culture and Antigen testing was performed. Histoplasma Capsulatum can present in immunocompetent individuals and a strong suspicion must be made in patients with history of travel to endemic areas. Pathologist needs to look for the yeast cells even in immunocompetent individuals while routine screening of the BAL fluid cytosmears. Special staining may be resorted to, in individuals with high suspicion and positive history. Confirmation may be done by fungal cultures and antigen testing.